ANTIMICROBIAL ACTIVITIES OF Shorea foxworthyi Sym STEAM BARK METHANOL EXTRACT - Andi Hairil Alimuddin; Masriani Masriani (Universitas Gadjah Mada, 2008)
Screening of antimicrobial activity compound from steam bark of Shorea foxworthyi Sym by Thin Layer Chromatography-Bioautography method have been conducted. The result of this research can be base in elucidation of antimicrobial activity compounds from S. foxworthyi Sym. The first step was done in this research that is maceration of S. foxworthyi steam bark using methanol solvent. Fractination to methanol extract was done using n-hexane, chloroform, and ethyl acetate solvent, respectively. Phytochemical screening were done to methanol, chloroform, n-hexane, and ethyl acetate fractions. Screening of antimicrobial activity compound were done to polar fraction such as methanol, chloroform, and ethyl acetate fraction. The bacteria were used in this screening such as E. coli, S. aureus, S. thypii, and B. Subtilis. The extract was highest antimicrobial activity choosed to test by Thin Layer Chromatography-Bioautography. The result was showed that chloroform extract was had highest antimicrobial activity and the flavonoide of compaund was considered having antimicrobial activity.